NILAI INFORMASI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN: ANALISIS EMPIRIK REGULASI INFORMASI DI INDONESIA - Ainnn Na'im (Journal of Indonesian Economy and Business (JIEB), 1999)
This study examined the information regulatory noncompliance (IRN) in Indonesia. The study investigates the effects of size, profitability, and financial distress on information regulatory noncompliance (IRN) affirms listed in the Jakarta Stock Exchange (JSX). The firms' IRN in this study is measured by the firm noncompliance on the timeliness regulation, i.e. whether firms submit financial statement to the Indonesian Capital Market Supervisory Agency (BAPEPAM) on, before, or after the due date. Submissions after the due date are considered as noncompliames, while submissions on or before the due date are considered as compliances. The contribution of this study is to provide preliminary empirical evidences about the timeliness of financial reporting which is still very limited in emerging market such as Indonesia. Indonesia has a different regulatory environment from those of the U.S. and other developed countries, so that the investigation of the timeliness provides more insight in financial accounting literature. Based on a sample of 56 firm years, this study found that return on asset (ROAj is a determining factor to noncompliance behavior of the firms in meeting the timeliness requirement. Inconsistent with previous studies (e.g., Whittred 1980 and Givoly and Palmon 1982), this study found that auditor opinion has no association with the noncompliances since most of the financial statements of noncomplied firms have unqualified opinions. The results are partially consistent with previous studies such as those of Schwartz and Soo (1996), Givoly and Palmon (1982) and Whittred(1980). Small sample size is one limitation of this study. This study used much less data than those used by previous studies conducted in the US and Australia. This study may be extended to include some other variables regarding the financial information regulation such as extent of disclosure and accounting choices. The market reaction to the IRN is another alternative topic to extend this study.